Pethik Laut Tradition as a Ritual of Repelling Bala (Study of Sociology Disaster) - Rahma, Rosselina Mulya (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
Indonesia is an archipelagic country that is famous for its ethnic, racial, religious and cultural diversity. This diversity is widespread in every area from Sabang to Merauke. The diversity of ethnicity, race, religion, and culture is in line with the many traditions that exist in every region in Indonesia. Each region has traditions and rituals that have their own meaning and purpose. One of them is the sea picking tradition carried out by the Muncar community, Banyuwangi Regency. This tradition has its own meaning and purpose for the people around Muncar. This study uses a qualitative research method with a case study approach. This study aims to analyze the Petik Laut tradition with the perspective of the sociology of disaster. The results of this study indicate that the Picking Laut tradition carried out by the Muncar community is a ritual to ask for safety for fishermen to avoid disasters while looking for fish in the sea